Ayurvedic Intervention in Primary Infertility due to Anovulatory PCOS (Beeja Dushti Janya Stree Vandhyatva) - Yashoda Kanwar; Hetal. H. Dave (AYUSHDHARA, 2025)
Modern-day stressors, inadequate consumption of nutritious organic foods, and changing lifestyle patterns have contributed to the rise of infertility as a significant health issue. Among individuals of reproductive age, infertility related to anovulation has become a major concern, largely attributed to unfavorable lifestyle changes. Remarkably, Polycystic Ovary Syndrome (PCOS) is the primary cause in 90% of these cases. The ancient wisdom of Ayurvedic scholar Sushruta remains relevant today, with his identification of four crucial factors for conception still holding true. Of these factors, ovum health is particularly significant, and disturbances in Vata Dosha often manifest as ovulatory dysfunction. Material & Methods: This case study focuses on a 27-year-old female patient who visited the Stree Roga and Prasuti Tantra OPD at NIA, Jaipur. Her primary complaint was the inability to conceive for 1.5 years, accompanied by a history of irregular menstruation since menarche. The study evaluated the effectiveness of Shaman therapy in treating infertility caused by ovulatory dysfunction. Result: The Ayurvedic treatment yielded impressive results, with the patient successfully conceiving within just three and a half months of beginning the therapy. Discussion: The treatment approach aimed to enhance ovum potency, regulate the menstrual cycle, promote Vataulomana, achieve Shrotoshudhi, and stimulate Artavajanan. Conclusion: Ayurvedic therapy shows promise in treating infertility caused by PCOD, offering positive outcomes without observed adverse drug reactions.